Studies on anti-microbial activity of Quisqualis indica L. plant extracts on urinary tract infection causing pathogens - Braja, S B; Shasank, S S; Padhy, R N; Sudhir , K P; Tahziba , H; Sanghamitra , P (Plant Science Today, 2026)
The ornamental plant, Quisqualis indica L. has several pharmacognistic properties. The anti-bacterial activity of the plant extracts against common bacteria causing Urinary tract infections (UTIs) were determined. In this study, Quisqualis Indica L. plant samples were collected during the spring season from Kalahandi District of Odisha. The different solvent extracts of the medicinal plant, Q. indica were used for determining the anti-bacterial activity against human pathogenic micro-organisms isolated from samples of patients having UTIs. In all, urine samples from 110 patients having UTIs were analyzed. Antibiotic susceptibility of gram-positive and gram-negative bacterial isolates was studied. The Molsoft tool was used to identify the drug likeness score of each compound. Escherichia coli was observed in 57 %, Pseudomonas aeruginosa in 17 %, Staphylococcus aureus in 15 % and Klebsiella pneumoniae in 10 % of the samples. Escherichia coli was the most predominant bacteria isolated from UTIs. Seven bacterial strains were used in the study namely Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Streptococcus pyogenes and Acinetobacter baumannii. The extracts of Q. indica have significant anti-bacterial properties against Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii and Streptococcus pyogenes causing the UTIs. The compounds mainly Phytol, Trans-sequalene, Tocoferol, Vitamin-E-acetate and stigmasterol have higher drug likeness scores. Our study has reported the structural configuration of the extracts having higher drug-likeness score with a potential for future therapeutic drug against the UTIs. This study focusses on UTIs and the phytochemical analysis has been evaluated with drug likeness score.